Here's Hank 5, There's a zombie in my bathtub / y Henry Winkler & Lin Oliver ; illustrated by Scott Garrett. - Winkler, Henry, 1945-; Oliver, Lin.; Garrett, Scott (New York : Grosset & Dunlap, an imprint of Penguin Random House, 2015)
"With Halloween approaching, Hank and his friends decide to watch a scary movie to get ready for the holiday. But the movie turns out to be a bit too scary for Hank, and suddenly he sees zombies every time he closes his eyes. Everyone says zombies are not real, but then people around him start moaning and acting like the undead, and he is not so sure. Hank is not taking any chances--not when there might be zombies on the loose!"--
Typeset in Dyslexie font B. V., developed by Dutch graphic designer Christian Boer specifically for people with dyslexia. It is designed to make letters more distinct from one another and to keep them tied down, so to speak,so that the reader is less likely to flip them in their minds. The letters of the font are also spaced wide apart to make reading them easier.
560
Accelerated Reader AR
Keywords: Halloween -- Juvenile fiction; Zombies -- Juvenile fiction; Humorous stories